Implementation of the Singing Method in Improving Arabic Vocabulary Mastery - Abdul Haris; Lala Latifah; Ayat Ruhiyat; Dini Akmaliah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Language is a characteristic that distinguishes humans from other creatures, so that language has become a human characteristic. These results show 1) There are differences in the learning outcomes of Arabic vocabulary mastery for class VI students as the experimental group (the group that uses the singing method in vocabulary learning 3) Based on the results of the questionnaire that the author gave to class VI MI Miftahul Huda Tasikmalaya students as the experimental group, it can be seen that based on the questionnaire, almost all students liked Arabic, although almost all also stated that learning Arabic vocabulary was indeed difficult. Most of the students had never used the singing method before in learning Arabic vocabulary. After being taught Arabic vocabulary using the singing method, most of the students stated that the singing method was interesting and that the singing method needed to be used in learning Arabic vocabulary.